2009
DOI: 10.1242/jeb.028886
|View full text |Cite
|
Sign up to set email alerts
|

Endurance capacity of mice selectively bred for high voluntary wheel running

Abstract: SUMMARYMice from four lines bred for high voluntary wheel activity run ~3-fold more revolutions per day and have elevated maximal oxygen consumption during forced treadmill exercise, as compared with four unselected control (C) lines. We hypothesized that these high runner (HR) lines would have greater treadmill endurance-running capacity. Ninety-six mice from generation 49 were familiarized with running on a motorized treadmill for 3 days. On days 4 and 5, mice were given an incremental speed test (starting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 85 publications
9
100
1
Order By: Relevance
“…Duman et al (2008) speculated that reduced locomotion in the open-field that was possibly related to immediate fatigue after running (see also Fuss et al 2010). This seems unlikely to us, however, as even our HR mice do not run voluntarily on wheels at speeds that exceed their maximal aerobic capacity Rezende et al 2005), nor do they show obvious signs of fatigue during or following wheel running (Meek et al 2009;personal observations). Alternatively, voluntary wheel running induces a significant elevation in circulating corticosterone in both HR and C mice (Girard and Garland 2002) and in C57BL/ 6N mice (Droste et al 2003).…”
Section: Genetic Correlations and Correlated Responses To Selectionmentioning
confidence: 86%
“…Duman et al (2008) speculated that reduced locomotion in the open-field that was possibly related to immediate fatigue after running (see also Fuss et al 2010). This seems unlikely to us, however, as even our HR mice do not run voluntarily on wheels at speeds that exceed their maximal aerobic capacity Rezende et al 2005), nor do they show obvious signs of fatigue during or following wheel running (Meek et al 2009;personal observations). Alternatively, voluntary wheel running induces a significant elevation in circulating corticosterone in both HR and C mice (Girard and Garland 2002) and in C57BL/ 6N mice (Droste et al 2003).…”
Section: Genetic Correlations and Correlated Responses To Selectionmentioning
confidence: 86%
“…In fact, recent work in human 'ultra-endurance' athletes (Pearson, 2006) suggests that neurobiological attributes make a greater contribution to maximum performance ability than has previously been acknowledged (Kayser, 2003;Baden et al, 2005;Noakes, 2007;Rose and Parfitt, 2007;Noakes, 2008). In our laboratory, selection for high voluntary wheel running in outbred laboratory house mice has been ongoing for more than 60 generations, and has resulted in numerous physiological (Girard et al, 2007;Malisch et al, 2008;Gomes et al, 2009;Meek et al, 2009), behavioral (Rhodes et al, 2001Rhodes and Garland, 2003; Belke and Garland, 2007;Meek et al, 2010), and neurobiological (Rhodes et al, 2003a;Rhodes et al, 2003b) changes in four replicate high-runner (HR) lines of mice as compared with four non-selected control (C) lines. Moreover, a recent comparative study demonstrated a positive correlation between brain size and an index of exercise capacity, maximal oxygen consumption (Raichlen and Gordon, 2011), one of the traits that has increased in the HR lines (Rezende et al, 2006b;Kolb et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…As compared with C mice, HR mice exhibit various anatomical (Garland and Freeman, 2005;Kelly et al, 2006) and physiological differences (Rezende et al, 2006a;Rezende et al, 2006b;Gomes et al, 2009;Meek et al, 2009) that appear to support their 2.5-to 3-fold greater daily wheelrunning distances. Although previous studies have revealed physiological (Dumke et al, 2001;Rezende et al, 2006a;Rezende et al, 2006b;Gomes et al, 2009;Meek et al, 2009;Kolb et al, 2010), morphological (Garland and Freeman, 2005;Kelly et al, 2006) and motivational (Rhodes et al, 2005; Belke and Garland, 2007) components underlying this HR phenotype, the present findings are the first evidence of neuroanatomical changes in the HR lines. [A previous study that quantified volume of the dentate gyrus of the hippocampus found no statistical difference between the HR and C lines (Rhodes et al, 2003a). ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Various changes in locomotor performance, behavior and neurobiology (especially related to motivation for wheel running) have been observed in the HR lines. [10][11][12] For instance, treadmill endurance capacity is elevated in HR mice, 13 as is maximal oxygen consumption. 14 Despite the continued selection since generation 16, HR mice seem to be at a selection limit, the biological causes of which are not yet clear.…”
Section: Introductionmentioning
confidence: 99%